LANDSCAPE PLANNING FOR THE SILEME-LEME PANORAMA TOURIST AREA IN POLLUNG SUBDISTRICT, HUMBANG HASUNDUTAN REGENCY - Rahmadhani Fitri; Purba, Ricky Wahyu (PT. Arsil Reka Engineering, 2025)
Panorama Sileme-Leme is a tourist destination in Humbang Hasundutan Regency, specifically in Huta Sileme-Leme, Parsingguran 2 Village, Pollung District, located at an altitude of approximately 1,600 meters above sea level. The beautiful natural panorama with Lake Toba as its backdrop and surrounded by expansive plantations makes it an ideal recreational spot. However, the supporting facilities in this area are insufficient to accommodate various recreational activities that could potentially be conducted there. Therefore, landscape planning and the provision of tourist facilities are necessary to make the area more attractive to visitors. The initial idea behind this concept is to plan the Sileme-leme Panorama area as an attractive tourism destination equipped with various supporting facilities for tourism activities. However, because it is located in a hilly area prone to landslides, the concept of a pine forest tourism area was implemented. In addition to enhancing aesthetics and visitor comfort, its primary function is to minimize landslides because pine trees are known as effective soil-stabilizing vegetation. In addition, the pine forest tourism landscape can also have interesting spots such as tall, shady pine trees, restaurants or cafes with views of the pine forest, and also play areas for children. This helps enhance the visitor's tourism experience and makes them feel close to nature and the beauty of the pine forest. The planning of the Sileme-leme Panorama Area uses a semi-pine forest concept supplemented with various tourism facilities. The implementation of this concept has been considered through various analyses conducted previously. With the implementation of the semi-pine forest concept, it is hoped that the natural potential will not change significantly, and the preservation of nature in this area will remain intact. This planning is expected to make Panorama Sileme-leme a more developed tourist attraction and more appealing to visitors. Additionally, this planning is anticipated to boost the local community's economy.